'Cancer Coiffures': Embodied Storylines of Cancer Patienthood and Survivorship in the Consumerist Cultural Imaginary. (December 2018) - Williams, Seán M; Solbrække, Kari Nyheim
Cancer patienthood and survivorship are often narrated as stories about hair and wigs. The following article examines cultural representations of cancer in mainstream memoirs, films, and on TV across Western European and American contexts. These representations are both the ideological substrate and a subtly subversive staging of a newly globalized cancer culture that expresses itself as an embodied discourse of individual experience. Wigs have become staples of an alternative story of especially women's cancer experience, one that contrasts with the advertising slogans of what has been termed 'Cancer Inc.' But wigs are also a prop for consumerist self-(re)invention and can be appropriated stereotypically, with regard to stock gendered expectations – despite and alongside their subversive potential.